Optimizing management of upper tract urothelial carcinoma - Campbell, Matthew T.; Shah, Amishi Y.; Matin, Surena F.; Siefker-Radtke, Arlene O. (Urologic oncology, 2017)
Upper tract urothelial cancer (UTUC) is a rare cancer of the urothelium, comprising only a fraction of cases as compared to urothelial tumors of the bladder. As a result, systemic treatment approaches in bladder cancer are often applied to patients with UTUC. Given the anatomical location of these tumors, the age, the comorbid conditions of these patients with UTUC, and the need for radical nephroureterectomy for treatment, most patients have substantial impairment of renal reserve. There is growing evidence for the benefit of perioperative chemotherapy in this disease. Patients with UTUC have high rates of microsatellite instability and fibroblast growth factor receptor 3 mutations as compared to their bladder counterparts presenting unique, important subsets in UTUC. Immune checkpoint inhibitors targeting the programmed death receptor 1 and ligand have provided a new second-line treatment option for patients with UTUC and appear particularly well suited for patients with microsatellite instability. More work in understanding the molecular gene signatures and its relationship to response to chemotherapy, immunotherapy, and targeted therapy is needed to continually optimize care for patients with all stages of disease. Advances in UTUC are possible, when one accounts for the unique clinical and biological features of this disease.